Public Service Advertisements: Emotions and Empathy Guide Prosocial Behavior - Bagozzi, Richard P.; Moore, David J. (Journal of Marketing, 1994)
The authors develop and test a theory of how public service advertisements function to induce helping responses. Building on Lazarus's general theory of emotion and adaptation, they hypothesize that public service ads designed to reduce the incidence of child abuse stimulate negative emotions; these, in turn, lead to empathic reactions and end with the decision to help. Two field experiments are conducted to test the theory.